Efficacy and safety of basal insulin degludec 100 IU/mL versus glargine 300 IU/mL for type 1 diabetes: the single-center INEOX randomized controlled trial. - Ruiz de Adana Navas, María Soledad; Domínguez, Marta Elena; Morillas, Virginia; Colomo, Natalia; Vallejo Mora, María del Rosario; Guerrero, Mercedes; García-Escobar, Eva; Carreira-Soler, Mónica; Romero-Zerbo, Silvana Yanina; Linares, Francisca; González-Mariscal, Isabel; Bermúdez Silva, Francisco Javier; et al. (Elsevier, 2023)
Aims To compare efficacy and safety of degludec 100 IU/mL (Deg-100) and glargine 300 IU/mL (Gla-300) in adults with type 1 diabetes. Methods Open-label, single-center, randomized, parallel-group, 24-week trial in adults with type 1 diabetes, on basal-bolus insulin therapy, HbA1c ≤ 10%, using self-monitoring blood glucose. Participants were randomized 1:1 to a basal-bolus insulin regimen with Deg-100 (N = 129) or Gla-300 (N = 131). Primary efficacy endpoint: mean change in HbA1c from baseline to week-24. Main safety outcome: incidence rate of hypoglycemia during the study. Quality of life (DQOL) and satisfaction with diabetes treatment (DTSQ) were assessed. Results At week 24, after adjusting for baseline HbA1c, the decrease in HbA1c did not differ between groups: Deg-100 (−0.07 ± 0.7%) and Gla-300 (−0.16 ± 0.77%) (P = 0.320). There were no significant differences between groups in HbA1c, nocturnal hypoglycemia, severe hypoglycemia, DQOL, or DTSQ scores. The incidence rates of hypoglycemia < 3.9 mmol/L (Deg-100: 115.24 events/person-year vs Gla-300: 99.01 events/person-year, p < 0.001); and < 3.0 mmol/L (Deg-100: 41.17 events/person-year vs Gla-300: 34.29 events/person-year, p < 0.001) were different between groups. Conclusions Deg-100 and Gla-300 have similar metabolic efficacy, incidence ratio of nocturnal and severe hypoglycemia, DQOL and DTSQ scores. Differences in the incidence rate of hypoglycemia < 3.9 mmol/L and < 3.0 mmol/L should be confirmed.
Keywords: Diabetes - Tratamiento; Type 1 diabetes; Glargine U-300; Degludec U-100; Clinical trial